2000
DOI: 10.1093/bioinformatics/16.1.34
|View full text |Cite
|
Sign up to set email alerts
|

History of the enzyme nomenclature system

Abstract: Naming things is essential for people to understand one another, no matter what language or field of interest is involved. This is as true for enzymes, genes and chemicals as it is for birds, food, flowers, etc. Effective communication requires a lack of ambiguity, but, in practice, ambiguities abound even between people who use the same language in different parts of the world, or even within the same country. Whereas ambiguities in the words used for common objects or actions have been the basis for many, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(65 citation statements)
references
References 1 publication
0
64
0
1
Order By: Relevance
“…The proposal of GO is to characterize the gene product by ontologies rather than by function nomenclature (molecular name) as it is done in this work (Chitale and Kihara, 2011;The Gene Ontology Consortium, 2013). The function nomenclature is the role of the protein in the organism in which it is expressed (Tripton and Boyce, 2000) and it is present in the "definition" field of the GenBank format file (file format for gene sequences) or GenPept (format file for protein sequences) in NCBI (U.S. National Library of Medicine, 2014). The contingency table methodology used in other assessments needs to reduce the classifications into two classification categories and only allows the assessment of one program and one dataset at each time (Thomas et al, 2003a;Prati et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The proposal of GO is to characterize the gene product by ontologies rather than by function nomenclature (molecular name) as it is done in this work (Chitale and Kihara, 2011;The Gene Ontology Consortium, 2013). The function nomenclature is the role of the protein in the organism in which it is expressed (Tripton and Boyce, 2000) and it is present in the "definition" field of the GenBank format file (file format for gene sequences) or GenPept (format file for protein sequences) in NCBI (U.S. National Library of Medicine, 2014). The contingency table methodology used in other assessments needs to reduce the classifications into two classification categories and only allows the assessment of one program and one dataset at each time (Thomas et al, 2003a;Prati et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…EC-(Enzyme Commission) numbers thus consist of 4 numbers, where at each level, the number denotes to which category the enzyme belongs. A review of the development of the enzyme nomenclature and classification can be found in Tipton and Boyce [14]. For future reference, we will make a few definitions.…”
Section: Estimation Of Correctness Using Enzyme Classificationmentioning
confidence: 99%
“…PPARD only has one original article 12 . According to SCI there are 198 13 articles that refer to this article, but we could only obtain reference lists for 154 14 of them. In these 154 reference lists, we identified 187 unique original articles and each of them represents one gene symbol that has been co-referred with the original article of PPARD.…”
Section: Assessment Of Completeness Using Sci Citation Datamentioning
confidence: 99%
“…A timeline of historic events in biocatalysis and biotechnology is outlined in Table 1. [18][19][20] Reviews and Accounts Novel methodologies for discovering industrial enzymes based on genomic sequencing and phage display (discussed further in Section 1.3), 21,22 as well as highly effective optimisation tools based on chemical, physical and molecular biology approaches, 23 have improved the access to biocatalysts, increased their stability, and radically broadened their specificity. …”
mentioning
confidence: 99%